The Technology Acceptance Models in Preventive Maintenance System Utillity in Pharmaceutical Industry - Kiki Hendarsyah; Didit Damur Rochman (Community Engagement and Emergence Journal (CEEJ), 2026)
PT XYZ has implemented digital transformation through the development of an Electronic Equipment Management System (E-EMS) in response to the need for effective and efficient manual recording and preventive maintenance utilities in the GMP area. This web-based application integrates all data components as well as preventive maintenance schedules and reports, thereby strengthening inspection readiness and compliance with Good Manufacturing Practices (GMP). However, the extent to which the adoption of E-EMS, attitudes toward its use, and utilization of the system affect GMP indicators remains unknown. This study aims to analyze the influence of perceived ease of use (PeoU) on perceived usefulness (PU) and attitude toward using (ATU), and behavioral intention to use (BItU) on actual system usage (ASU) as indicators of GMP achievement. The method used is a quantitative approach with an explanatory survey design to test the relationship between constructs. It also includes social influences and cognitive-instrumental processes such as subjective norm, image, job relevance, output quality, and result demonstrability, with experience and voluntaries as contextual factors that can influence the relationship between variables in the Technology Acceptance Model (TAM2). Data were collected through structured questionnaires and analyzed using Descriptive Analysis and Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that perceived usefulness (PU) is significantly influenced by output quality (OQ), result demonstrability (RD), and job relevance (JR). The social factors of subjective norm (SN), image (Im), and experience (Ex) have no direct effect. Perceived ease of use (PEoU) has a positive and significant effect on perceived usefulness (PU). Employee attitudes are more influenced by ease than benefits (PEoU ® ATU), while PU ® ATU is not significant, meaning that PT XYZ employees have a positive attitude toward E-EMS when the system feels practical and not difficult, not because the system is useful. However, the attitude of continuous use intention arises when the system has positive and convenient characteristics driven by ease.